Volume 1: Additive Manufacturing; Advanced Materials Manufacturing; Biomanufacturing; Life Cycle Engineering; Manufacturing Equ 2020
DOI: 10.1115/msec2020-8253
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Analysis of ABS From Hybrid Additive Manufacturing by Fused Filament Fabrication and Shot Peening

Abstract: The mechanical properties of 3D printed polymers parts are process parameter dependent. Defects such as inadvertent voids between deposited rasters and layers lead to weakness in produced parts, which results in inferior mechanical properties as compared to injection molding. An alternative method to change energy absorption and stiffness of a polymer is hybrid additive manufacturing (AM). Hybrid-AM is the use of additive manufacturing with one or more secondary processes that are fully coupled and synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fracture strength of the composite gained from 25 to 57 MPa with the aid of vibrations. Hadidi et al [ 140 ] showed that shot peening coupled with FFF increased the dynamic mechanical characteristics of ABS 430 thermoplastics. The compressive load enhanced the toughness of the samples.…”
Section: Post‐processing Techniquesmentioning
confidence: 99%
“…Fracture strength of the composite gained from 25 to 57 MPa with the aid of vibrations. Hadidi et al [ 140 ] showed that shot peening coupled with FFF increased the dynamic mechanical characteristics of ABS 430 thermoplastics. The compressive load enhanced the toughness of the samples.…”
Section: Post‐processing Techniquesmentioning
confidence: 99%